Mobilidade urbana e sua relação com as desigualdades sociais: um estudo de caso em Francisco Morato - SP - Pereira, Rosana Pedrosa (2022)
This thesis seeks to show the relationship between urban mobility and the social inequalities of a peripheral and impoverished population that needs to make trips for work, study, health, leisure, etc. but has difficulties to fund public transportation. This said and with the intention of deepening the discussion of the relationship between mobility/inequality, this thesis elected as the object of study the municipality of Francisco Morato, a dormitory city, located in the Northern Sub-region of the RMSP, where the phenomenon of pendulum mobility is observed mainly in the direction of the metropolitan region of São Paulo. The main purpose of this research is to defend the idea that urban mobility is one of the answers to reduce the phenomenon of social inequality and reproduction of poverty. Thus, the hypothesis is based on the idea that if the transport system does not supply or hinder the conditions of access to equipment for collective use, or to the places of greatest economic activity, the situations of social exclusion and reproduction of poverty are expanded. Having this idea of urban mobility as a variable to reduce social inequalities, the questioning that is the guide of this thesis is about: In her perception, if the mobility performed by public transport were different from what it is today, would it have the power to reduce the inequalities of opportunities for work, study, leisure and health? Why is that? To understand the dimension of this questioning, the following specific objectives were defined: to present and discuss the problems arising from disorderly urbanization in Francisco Morato; contextualize urban mobility and its relationship with social inequality; to analyze the context of sociospatial segregation and its relationship with pendulum mobility mainly for work and study main aspects for improving people's living conditions. Methodologically, aqualitative research was developed, using as an instrument of data collection the indepth interview in order to know the perception of residents about urban mobility and its relationship with social inequality in the city of Francisco Morato. As a result, the research shows that the solution to reduce social inequalities is to reconcile urban development planning with public transport planning, in this form will havethe results that the population wants andexpects from the public power. This implies: quality and low cost public transport, integration in the different modals, widening and reforms of sidewalks to allow the movement of people, paving streets with signs and speed bumps, encouraging companies and industries to settle in the city to generate employment and income avoiding unnecessary displacement, encourage partnerships with the "S" System, "Etecs" and "Fatecs", in order to qualify the workforce, creating leisure areas near people's homes, creating bike paths and bike racks to encourage the use of bicycles, among other points that were raised in the field research